A Critical Survey on Renewable Energy Applications in the Philippines and China: Present Challenges and Perspectives - Li, Xin; Wang, Haizhi; Lu, Yuanru; Li, Wanlin (Frontiers in Energy Research, 2021)
China's Belt and Road (B&R) initiative provides new ideas and opportunities for international cooperation. Renewable energy plays a crucial role not only in national sustainable development framework of China and the Philippines, but also in bilateral cooperation between them. However, there still exists some obstacles need to be tackled due to the fact that renewable energy cooperation between China and the Philippines has not been thoroughly and comprehensively studied at present. Based on in-depth analysis of current renewable energy cooperation between China and the Philippines, this paper employs PESTEL analysis to fully investigate cooperative advantages/disadvantages from the aspects of politics (P), economy (E), society (S), technology (T), environment (E) and legislation (L), upon which several constructive suggestions are proposed. The ultimate purpose is to design feasible schemes to ensure the sufficient utilization of renewable energy and construction of integrated power grid system to meet the shortage of electricity supply especially in the isolated small islands in the Philippines through cooperation with China. In particular, it offers valuable advice against U.S.-China trade war and COVID-19 pandemic, which is significant to exploit potential renewable energy cooperation.